The Validity of the Termination of Corruption Cases Based on the Memorandum of Understanding between the Government Internal Supervisory Apparatus and Law Enforcement Apparatus - Hadya Zuhra; Dahlan Dahlan; Iskandar A. Gani (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The number of corruption cases in Indonesia continues to increase. The termination of the investigation of alleged corruption at the Aceh Truth and Reconciliation Commission by the Banda Aceh City Resort Police based on a Memorandum of Understanding between the Government Internal Supervision Apparatus and Law Enforcement Apparatus raises problems because it is contrary to the Law on the Eradication of Corruption Crimes which emphasizes that the return of state losses does not erase the crime. This inconsistency raises questions about the validity of stopping corruption cases through the Memorandum of Understanding. This study aims to assess the validity of the Memorandum of Understanding between the Government Internal Supervision Apparatus and the Law Enforcement Apparatus as the basis for stopping corruption cases, as well as to outline the legal process that should be taken by the Banda Aceh City Resort Police. This research uses a normative juridical method with a legislative, case, and conceptual approach, based on secondary data from various legal materials. The analysis was carried out in an analytical descriptive manner. The results of the study show that the Memorandum of Understanding between the Government Internal Supervision Apparatus and the Law Enforcement Apparatus cannot be the basis for the termination of corruption cases at the Aceh Truth and Reconciliation Commission because it is only coordinated, not a source of criminal law. The note is only suitable for use to follow up on reports through audits. In addition, the Banda Aceh City Resort Police should continue the case to the investigation stage because the elements of corruption, evidence, as well as elements of mens rea and actus reus have been fulfilled without any justification or excuse. It is suggested that the memorandum of understanding can only be a coordinating guideline, not a basis for stopping corruption cases. Any report must still be processed, and the Banda Aceh City Resort Police are obliged to continue the investigation even though the state losses have been returned.